Penguatan Nilai Luhur Warisan Budaya Kajian Adat Istiadat Pernikahan Jawa Pasca Pandemi Covid-19 di Kota Surakarta - Yustina Denik Risyanti; Enik Rahayu (Jayapangus Press, 2023)
The procession of the Javanese wedding ceremony ceremony in Surakarta is a cultural heritage from the palace which until now has maintained its existence, has its own uniqueness and characteristics that other regions do not have. This study aims to describe and analyze the internalization of the noble values of local wisdom through the procession of Javanese wedding customs in Surakarta City after the Covid-19 pandemic. Data were collected using a qualitative descriptive method through participatory observational interviews with informants. by involving senior makeup artists, users of customs. The results of the study show that the procession of the wedding ceremony of Javanese Surakarta wedding customs through a series of preparations, core, and plenary. Each stage of the procession has values and meanings contained in symbols including: religious, social and personal values. The conclusion is that the procession of the Javanese Surakarta wedding ceremony is carried out in a coherent manner, which is passed step by step. Each stage of the procession has a noble value and meaning contained in the symbol as a guide in building a household.